2008
DOI: 10.1158/1940-6207.capr-08-0084
|View full text |Cite
|
Sign up to set email alerts
|

Gemini Vitamin D Analogues Inhibit Estrogen Receptor–Positive and Estrogen Receptor–Negative Mammary Tumorigenesis without Hypercalcemic Toxicity

Abstract: Numerous preclinical, epidemiologic, and clinical studies have suggested the benefits of vitamin D and its analogues for the prevention and treatment of cancer. However, the hypercalcemic effects have limited the use of 1α,25(OH) 2 D 3 , the hormonally active form of vitamin D. To identify vitamin D analogues with better efficacy and low toxicity, we have tested >60 novel Gemini vitamin D analogues with a unique structure of two side chains for growth inhibition of breast cancer cells. Our initial studies foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 46 publications
5
51
0
Order By: Relevance
“…Therefore, numerous synthetic vitamin D 3 analogs have been developed for better anticancer efficacy with lower toxicity (Hines et al, 2010). Our studies demonstrated that Gemini vitamin D analogs inhibited the formation and growth of estrogen receptor-positive mammary tumors in vivo without hypercalcemic toxicity (Lee et al, 2008) and suppressed mammary tumor growth in the ErbB2-overexpressing transgenic mice . In the present study, because of the importance of CD44 as a cancer stem cell marker and its suggested functional roles in breast cancer, we examined the effects of Gemini BXL0124 on regulation of CD44 in cultured MCF10DCIS.com cells in vitro and in MCF10DCIS.com xenograft tumors in vivo.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Therefore, numerous synthetic vitamin D 3 analogs have been developed for better anticancer efficacy with lower toxicity (Hines et al, 2010). Our studies demonstrated that Gemini vitamin D analogs inhibited the formation and growth of estrogen receptor-positive mammary tumors in vivo without hypercalcemic toxicity (Lee et al, 2008) and suppressed mammary tumor growth in the ErbB2-overexpressing transgenic mice . In the present study, because of the importance of CD44 as a cancer stem cell marker and its suggested functional roles in breast cancer, we examined the effects of Gemini BXL0124 on regulation of CD44 in cultured MCF10DCIS.com cells in vitro and in MCF10DCIS.com xenograft tumors in vivo.…”
Section: Introductionmentioning
confidence: 73%
“…Our recent report of in vivo and in vitro inhibitory activities of novel Gemini vitamin D analogs on MCF10DCIS.com cells (Lee et al, 2008) led us to study whether 1␣,25(OH) 2 D 3 or Gemini vitamin D analogs regulate cancer stem cell markers such as CD44, which eventually results in inhibition of breast tumorigenesis. 1␣,25(OH) 2 D 3 is the key hormone in calcium/phosphate homeostasis and bone mineralization, and an epidemiological study indicates an association between low serum vitamin D levels and increased risk for breast cancer (Deeb et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This has led to the search for new vitamin D analogs that retain the antiproliferative and prodifferentiative properties of 1,25(OH) 2 D3 but are not calcemic (Masuda and Jones, 2006;Takahashi and Morikawa, 2006;Lee et al, 2008;Slominski et al, 2010). Vitamin D analogs that have such properties are produced by the action of cytochrome P450scc (CYP11A1) on vitamin D Wang et al, 2012), and several of them show antimelanoma activity in cell culture models Slominski et al, 2012aSlominski et al, , 2013b.…”
Section: Introductionmentioning
confidence: 99%
“…However, the supraphysiological doses required for the anticancer effects result in toxic hypercalcemia, which limits the use of 1,25(OH) 2 D 3 for therapeutic purposes. As a result, other vitamin D analogs are being tested that retain the antiproliferative and prodifferentiative properties of 1,25(OH) 2 D 3 but are not calcemic (Masuda and Jones, 2006;Takahashi and Morikawa, 2006;Lee et al, 2008;Slominski et al, 2010). A new source of vitamin D analogs with such properties arises from the action of cytochrome P450scc on vitamin D 3 (Slominski et al, 2006;Zbytek et al, 2008;Janjetovic et al, 2009;Slominski et al, 2010).…”
Section: Introductionmentioning
confidence: 99%